Structural Changes Associated with Delayed Dark Adaptation in Age-Related Macular Degeneration - Laíns, Inês; Miller, John B.; Park, Dong H.; Tsikata, Edem; Davoudi, Samaneh; Rahmani, Safa; Pierce, Jonathan; Silva, Rufino; Chen, Teresa C.; Kim, Ivana K.; Vavvas, Demetrios; Miller, Joan W.; et al. (Ophthalmology (Rochester, Minn.), 2017)
To examine the relationship between dark adaptation (DA) and optical coherence tomography (OCT)–based macular morphology in age-related macular degeneration (AMD). Prospective, cross-sectional study. Patients with AMD and a comparison group (>50 years) without any vitreoretinal disease. All participants were imaged with spectral-domain OCT and color fundus photographs, and then staged for AMD (Age-related Eye Disease Study system). Both eyes were tested with the AdaptDx (MacuLogix, Middletown, PA) DA extended protocol (20 minutes). A software program was developed to map the DA testing spot (2° circle, 5° superior to the fovea) to the OCT B-scans. Two independent graders evaluated the B-scans within this testing spot, as well as the entire macula, recording the presence of several AMD-associated abnormalities. Multilevel mixed-effects models (accounting for correlated outcomes between 2 eyes) were used for analyses. The primary outcome was rod-intercept time (RIT), defined in minutes, as a continuous variable. For subjects unable to reach RIT within the 20 minutes of testing, the value of 20 was assigned. We included 137 eyes (n = 77 subjects), 72.3% (n = 99 eyes) with AMD and the remainder belonging to the comparison group. Multivariable analysis revealed that even after adjusting for age and AMD stage, the presence of any abnormalities within the DA testing spot (ß = 4.8, P < 0.001), as well as any abnormalities in the macula (ß = 2.4, P = 0.047), were significantly associated with delayed RITs and therefore impaired DA. In eyes with no structural changes within the DA testing spot (n = 76, 55.5%), the presence of any abnormalities in the remaining macula was still associated with delayed RITs (ß = 2.00, P = 0.046). Presence of subretinal drusenoid deposits and ellipsoid zone disruption were a consistent predictor of RIT, whether located within the DA testing spot (P = 0.001 for both) or anywhere in the macula (P < 0.001 for both). Within the testing spot, the presence of classic drusen or serous pigment epithelium detachment was also significantly associated with impairments in DA (P ≤ 0.018). Our results suggest a significant association between macular morphology evaluated by OCT and time to dark-adapt. Subretinal drusenoid deposits and ellipsoid zone changes seem to be strongly associated with impaired dark adaptation.